Saturation mutagenesis of a polyadenylation signal reveals a hexanucleotide element essential for mRNA 3' end formation in Saccharomyces cerevisiae. - Irniger, S (1994)
The cis-acting signal sequences required for mRNA 3' end formation are highly conserved and well characterized in higher eukaryotes. However, the situation in the yeast Saccharomyces cerevisiae is still unclear. Several sequences have been proposed which share only limited similarities. One difficulty in identifying yeast polyadenylylation signals might be the presence of redundant signal sequences in the 3' region of yeast genes. To circumvent this problem we have analyzed the heterologous 3' region from cauliflower mosaic virus which contains a yeast polyadenylylation signal. We have performed a saturation mutagenesis of the key element TAG-TATGTA, which is a condensed version of the polyadenylylation signal TAG ... TATGTA ... (TTT) which had previously been proposed. Each of the nine nucleotides was replaced by the three other possible nucleotides and all resulting 1-bp mutants were tested for their capacity to specify mRNA 3' end formation in yeast cells. The first three nucleotides of this condensed sequence are not required, but mutagenesis of the other six nucleotides had distinct effects on mRNA 3' end formation. All mutants that were significantly functional had the sequence TAYRTA, and the sequence TATATA had the best capacity for mRNA 3' end formation. The two thymidine residues at the first and fifth positions are the most essential nucleotides in this sequence. Our results suggest that a degenerate hexanucleotide is essential for mRNA 3' end formation in yeast. This is reminiscent of the conserved polyadenylylation signal in higher eukaryotes, AATAAA.